Corner-Cutting Subdivision Surfaces of General Degrees with Parameters (Journal of Computational Mathematics, 2020)
As a corner-cutting subdivision scheme, Lane-Riesefeld algorithm possesses the conciseand unified form for generating uniform B-spline curves: vertex splitting plus repeatedmidpoint averaging. In this paper, we modify the second midpoint averaging step of theLane-Riesefeld algorithm by introducing a parameter which controls the size of cornercutting, and generalize the strategy to arbitrary topological surfaces of general degree.By adjusting the free parameter, the proposed method can generate subdivision surfaceswith flexible shapes. Experimental results demonstrate that our algorithm can producesubdivision surfaces with comparable or even better quality than the other state-of-the-artapproaches by carefully choosing the free parameters.
Keywords: Lane-Riesenfeld algorithm; Spline curves; Subdivision curves/surfaces; Corner-cutting subdivision surfaces.